Criminal Threats against the Abuse of Bonded Zone Facilities - Agus Widodo; Arpangi Arpangi (Law Development Journal, 2021)
Bonded Zone is one form of facilities provided by the customs authority (Directorate General of Customs and Excise) to entrepreneurs in the form of a fiscal which aims to provide the maximum benefit for national economic growth as well as the usual form of treatment for international relations. Entrepreneurs using the Kawasan Beikat facility have the potential to abuse the facilities provided. This research is entitled Criminal Threats Against Misuse of Bonded Zone Facilities. The aim of this research is to find out whether the abuse of bonded zone facilities can be punished by crime and how the modes used by these 'naughty' businessmen are to divert or avoid import duties and taxes. The research method used is normative juridical. The conclusion of this research is that the entrepreneur who receives the facility can abuse the facility for the benefit of the entrepreneur or the interest of the individual so as to harm state revenue. Act No. 10 of 1995 concerning Customs in conjunction with Act No. 17 of 2006 concerning amendments to Act No. 10 of 1995 concerning Customs has regulated the criminal threats that can be imposed for the abuse of bonded zone facilities. The mode used is to reduce the actual / physical quantity of exported goods from the number of goods notified in the export document. It is as if the company has re-exported imported goods that have received facilities. But by them, not all of the imported goods are used for production / re-export but they are resold locally.